ARTIFICIAL INTELLIGENCE IN MEDICAL TRAINING AND DECISION-MAKING - Ikromova Sokinabonu Ravshanzoda; Nasirova Durdonaxon Yusufjon qizi; Shaismatova Gulbahor Xikmatovna (Modern American Journals, 2025)
Artificial Intelligence (AI) has become one of the most transformative technologies in modern healthcare and medical education. In medical training, AI offers innovative tools such as intelligent tutoring systems, virtual patients, and simulation-based platforms that improve clinical skills, diagnostic reasoning, and decision-making abilities of future doctors. Moreover, AI-driven algorithms provide evidence-based recommendations, assist in the interpretation of medical data, and support complex clinical decision-making processes. By combining big data analytics with machine learning, AI enables personalized learning for medical students and enhances accuracy in patient care. This article explores the role of AI in medical training and clinical decision-making, highlighting its benefits, challenges, and future perspectives in shaping the next generation of healthcare professionals.
Keywords: Artificial Intelligence, medical education, medical training, decision-making, machine learning, clinical practice, healthcare technology, simulation, virtual patients, intelligent tutoring systems.